The Demand for Accounting Conservatism for Management Control - KWON, Young Koan (Institutional Knowledge at Singapore Management University, 2001)
We show that conservative financial reporting arises naturally in principal-agent settings as a means of efficiently motivating agents when the penalties that can be imposed on agents are limited. We consider an accounting system whose reports are used for contracting and whose parameters are controlled by the principal. One advantage of our model is that the information system we describe has the accounting characteristic of mapping unbiased underlying information about the firm into a reduced message space. The principal can choose how that mapping operates, i.e., conservatively, liberally, or neutrally. When penalties are sufficiently limited (a limited liability setting), we show that the accounting system designed by the principal is always conservative. Alternatively, in an unlimited liability setting, any bias in the system depends on random circumstances, and we would not expect accounting conservatism to arise as a pervasive and enduring phenomenon. [PUBLICATION ABSTRACT]